Kajian Yuridis Organisasi Masyarakat Pada Komitmen Kehidupan Bermasyarakat dan Bernegara di Wilayah NKRI - Cornelis, Vieta I (Lex Journal: Kajian Hukum & Keadilan, 2017)
Freedom of association to gather and express opinion is apart of human rights in the life of nation and state in the country of Indonesia.The consept of article 1 act 2 UUD 1945 opens space of consequences which is the principle of democracy and law.The law is represented by law and repsentative democracy by the sovereignty of the people,it means that in the implementation of all the life of the state,democracy plays an important role for the state process.The amendment reforms clearly put the issue of appreciation for community organizatio. Then finally develoved the right of other rights,which then regulted more clearly in the article that has been amnademen article but still on the commitment that still run by the Law on conition that the destination of the country committed NKRI is the price of death.